Research of Psychological Factors of Development of Creative Self-Regulation of the Personality of Future Teachers - Gafurdjanovna Mukhamedova , Dilbar; Musinova Yunusovna, Rukhshona (International Journal of Psychosocial Rehabilitation, 2020)
The article examines the psychological factors of the development of creative self-regulation of personality in future teachers. The studied object of the experiment are university students. At the heart of creative self-regulation, the author considers the life-oriented conclusions arising from it can be used in the formation of the teaching staff